PENGARUHPENGALIHANPAJAKBUMI DANBANGUNANPERDESAAN DANPERKOTAAN TERHADAPBELANJAMODAL DENGANPENDAPATANASLIDAERAH SEBAGAIVARIABEL PEMODERASI (StudiEmpirispada Kabupaten/KotadiProvinsiAceh) - Zikri, Unazir Achmad; Asmara, Jhon Andra (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2016)
Thisstudyaimedto examinetheeffectofthetransitiontaxlandandbuildinginvillage and citytowards capitalexpenditurewithregionalrealrevenueasthemoderatingvariable.Thedatausedin thisresearchhis secondarydata.Thesamplewastakenby purposivesamplingmethodand thenumberofsamplesobtained were17 district/cityintheprovinceofAcehin2014 and 2015.Theanalysistechniqueusedismoderatedregression analysisusingSPSS 23.This study uses tax land and building in village and city as the independent variable and capital expenditureasthedependentvariable,andthenregionalrealrevenueasthemoderatingvariable.Theresultsof thisstudy indicatethatthe simultaneoustesting(testF),taxlandandbuildinginvillageandcityandregionalreal revenuehasaneffectoncapitalexpenditure.Inthepartialtest(ttest),variabletaxlandandbuildinginvillage andcityandregionalrealrevenuehasno effectoncapitalexpenditure.Keywords:Taxlandandbuildinginvillageandcity,capitalexpenditure,andregionalrealrevenue